Negation and the Left Periphery of the Clause in Persian Yes-No Questions: A Minimalist Approach - Hossein Moghani (مطالعات زبان‌‌ها و گویش‌های غرب ایران, 2017)
The aim of the present paper is to analyze the negative and interrogative interpretations in the yes-no questions in Persian in terms of which verb is preposed and moved to the left periphery of the clause under the influence of discourse–functional processes. The data of the study is collected from the spoken form of Standard Persian and the theoretical framework of the research is based upon the checking theory within the Minimalist Program (Chomsky, 1995, 2000, 2001a-b) as well as the Split-CP Hypothesis (Rizzi, 1997). To this end, first the claim is made that the preposed verb in the positive and negative yes-no questions lands in the head of FocP. Following that, it is proposed that due to the inability of the overt movement of the negative verb to the head of the ForceP to satisfy the question interpretation, the [+Q] on the verb moves alone to this head with an aim to check and value the [-Q] on the head of ForceP, leaving the [Neg] feature on the head of FocP. Such a mechanism guarantees that the [Neg] feature on the verb does not c-command the [+Q] feature and helps avoid generating an unacceptable and incoherent reading.